Intercultural pragmatic competence as a source of health inequities in monolingual interprofessional interactions: The case of Chile - Mariana Lazzaro-Salazar; Olga Zays-Spence (Discourse & Communication, 2026)
This article examines intercultural pragmatic competence as an under‑recognised source of health inequities in pluricentric, monolingual healthcare settings. Drawing on interactional sociolinguistics and the social determinants of health framework, the study analyses interview data from 40 migrant doctors working in public hospitals in Chile. Although migrant and local doctors share Spanish as a native language, differences in culturally grounded pragmatic norms, particularly preferences for direct and indirect communication styles, cause recurrent inter‑professional conflicts. Migrant doctors describe how these pragmatic divergences shape professional hierarchies, restrict participation in decision‑making and cause psychosocial stress. We argue that focusing on language proficiency alone obscures the role of intercultural pragmatic competence in producing linguistic and professional inequities in health. By focusing on same‑language intercultural encounters, the study expands the context of linguistic equity to interactions involving same language speakers. The findings position intercultural pragmatic competence as a critical, yet overlooked, social determinant of health affecting both healthcare professionals’ wellbeing and professional practice.